PENGARUH PEMBERIAN KEFIR BENING TERHADAP KADAR GLUKOSA DARAH PADA TIKUS WISTAR HIPERGLIKEMIA YANG DIINDUKSI STREPTOZOTOCIN (STZ) - Judiono Judiono; Endang Purwaningsih; RRJ. Djokomoeljanto; Suharyo Hadisaputro (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2009)
ABSTRACT Background: Hyperglycemia in diabetes caused by excessive free-radicals, which in turn increases reactive oxygen species, reduced immune function and antioxidant, the beta cell damage. Objective: To validate the effects of plain kefir probiotic on blood glucose level in streptozotocin (STZ) induced hyperglycemia Wistar rats. Methods: The experiment using randomized pretest-posttest control group design was carried-out on 48 male hyperglycemia Wistar rats induced by 40 mg/kg body-weight of STZ. Rats were divided randomly into four groups: (1) negative control fed ad libitum standard diet, (2) positive control induced by STZ, (3) insulin treated 0.76 UI/200 g body weight, and (4) plain kefir 3.6 cc per day. Kefir is prepared by the use of pasteurized skim milk fermented by kefir commercial inoculums. Blood glucose was measured with Super Glucocard II meter (Arkray, Kyoto, Japan). Results Kefir supplementation 3.6 cc per day had significantly effect on blood glucose reduction after… days. Results showed that blood glucose levels before and after the treatment in each group as follows: in negative control group, before and after the treatment were 92.7 ± 6.6 mgdL and 89.4 ± 5.3 mgdL, respectively; in positive control group, before and after treatment were 263.9 ± 61.7 mgdL and 290.9 ± 99.8 mgdL; in insulin group, before and after the treatment were 286.9 ± 73.2 mgdL and 168.3 ± 53.3 mgdL; and in kefir group, before and after the treatment were 234.0 ± 61.1 mgdL and 147.8 ± 52.6 mgdL. Conclusion: Kefir supplementation significantly reduced blood glucose in vivo. Isolation and identification of probiotic involved on biomolecular and to find out the role of specific probiotic originated from kefir in diabetes mellitus are very challenging to be implemented in clinical application. [Penel Gizi Makan 2009, 32(2): 129-136] Key words: probiotic, kefir, diabetes mellitus, hyperglicemia, streptozotocin